The role of the mawāli in the political developments of Kufa: A historical-social analysis - Gahremani, Reza (2021)
The objective of this research was to analyze the role of mawāli in the political developments in Kufa (Iraq). This article seeks to explain the role of the mawāli people in the interactions and political and social developments of Kufa by referring to reliable resources and examining the words of historians. The method of this research was descriptive-analytical which was done in a documental method using the available sources. The results showed that due to its complex and heterogeneous social structure, this city hosted various social strata that played a key role in political developments, including the mawāli. In the principle and theory of Islam, equality and brotherhood of Muslims are important. But this was not the case in practice and the mawāli were exposed to insult, contempt and prejudices of the Arabs. The mawāli were considered as slaves and second-class citizens by the Arabs because unlike the warlike Arabs, they farmed or worked as laborers, craftsmen, shopkeepers and merchants and tried to free them from slavery. Gradually, the mawāli gained a relatively important role and place and high positions in the administrative and military pillars so that many famous commanders and early Islamic scholars were mainly from the mawāli. These people made a great cultural influence on the Arabs.